Evaluation the results of colon transit time in patients with chronic constipation resistant to treatment - Anari, Hasan; Yazdanbod, Abbas; Sadeghieh-Ahari, Saeed; Rahimpourmiralilu, Ali (International Journal of Research in Medical Sciences, 2023)
Background: Determining colon transit time (CTT) is one of the simplest, reproducible, safe, inexpensive, reliable, patient-acceptable and fully applicable methods in the evaluation of patients with constipation. Objective was to determine the results of colon transit time (CTT) in patients with chronic drug resistant constipation. Methods: In this study, 30 people with constipation for at least three months and had defecation at most twice a week and did not respond to basic treatments were studied from October 2019 to June 2021 at Ardabil city hospital. 20 metal markers were given orally. Abdominal x-ray was performed on the 6th day and the number and speed of markers were considered. Patients also discontinued their anti-constipation medications. According to the CTT pattern, the causes of refractory chronic constipation were identified. Results: Of all 30 patients, 13 (43.3%) were male and 17 (56.7%) were female. The mean age of patients was 45.4 years with a standard deviation of 15.92. The greatest number of underlying diseases was related to blood pressure with 10 cases (33.3%). Of all patients, 19 patients (63.3%) had normal transit time colon despite chronic constipation. In terms of disorders; 5 patients (16.7%) had colon inertia, 3 patients (10%) had outlet obstruction and 3 patients (10%) had hindgut dysfunction. There was no significant relationship between colon transit time outcomes and patients’ gender and age. Conclusions: Examination of transit time colon in patients showed that the finding was normal in most of cases.